American journal on addictions
" ... covers a wide variety of topics ranging from codependence to genetics, epidemiology to dual diagnostics, etiology to neuroscience, and much more. Features of the journal, all written by experts in the field, include special overview articles, clinical or basic research papers, clinical updates, and book reviews within the area of addictions."